Anti-haemostatic compounds from the vampire snail Cumia reticulata: Molecular cloning and in-silico structure-function analysis. (August 2018) - Modica, Maria Vittoria; Reinoso Sánchez, Jonathan; Pasquadibisceglie, Andrea; Oliverio, Marco; Mariottini, Paolo; Cervelli, Manuela
Graphical abstract: Highlights: The vampire snail Cumia reticulata, revealed a complex mixture of proteins with potential anaesthetic and anticoagulant action. Based on full-length mRNA sequence cloned, it was possible to validate the coding sequence of five genes. The anticoagulant secreted proteins of Cumia reticulata have been characterized by bioinformatics methodologies. Abstract: Blood-feeding animals are known for their ability to produce bioactive compounds to impair haemostasis and suppress pain perception in the host. These compounds are extremely appealing for pharmacological development since they are generally very effective and specific for their molecular target. A preliminary RNA-Seq based characterization of the secretion from salivary and mid-oesophageal tissues of the vampire snail Cumia reticulata, revealed a complex mixture of feeding-related transcripts with potential anaesthetic and anticoagulant action. Based on the cloned full-length mRNAs, it was possible to verify the sequence of five genes encoding haematophagy-related products. The in silico modelled three-dimensional structure of each translational product was analysed to gain information on their potential biochemical activity. We have hereby validated and further investigated the assembled transcripts presumably involved in the antihaemostatic action, to improve our comprehensive understanding of this subset of the feeding secretion. The studied proteins included both inhibitors of primary haemostasis such as the vWFA domain-containing proteins, and compounds targeting different steps of the coagulation cascade, as e.g. the Turripeptide-like/protease inhibitor, the TFPI-like multiple Kunitz-type protease inhibitors, the Meprin-like metalloproteases and the Astacin/ShKT-like domain-containing proteins. All these molecules showed promising potential for pharmacological development.